2017
DOI: 10.1038/modpathol.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

EBV-negative aggressive NK-cell leukemia/lymphoma: a clinical and pathological study from a single institution

Abstract: Aggressive natural killer (NK)-cell leukemia/lymphoma is a systemic NK-cell neoplasm that preferentially affects Asians with a fulminant clinical course and is almost always associated with Epstein-Barr virus (EBV). The data on EBV-negative aggressive NK-cell leukemia/lymphoma are limited. Here we report a series of three patients (two Caucasians, one African-American) with EBV-negative aggressive NK-cell leukemia/lymphoma from a single institution, including a case diagnosed on post-mortem examination. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 32 publications
(63 reference statements)
1
35
0
Order By: Relevance
“…To date, only around one hundred cases have been reported all over the world and the main disease manifestations are in concordance with the patient presented herein. Comparable clinical and pathological features were observed in 3 cases of EBV-negative ANKL that were recently reported [ 12 ].…”
Section: Discussionsupporting
confidence: 70%
“…To date, only around one hundred cases have been reported all over the world and the main disease manifestations are in concordance with the patient presented herein. Comparable clinical and pathological features were observed in 3 cases of EBV-negative ANKL that were recently reported [ 12 ].…”
Section: Discussionsupporting
confidence: 70%
“…The term 'aggressive NK-cell leukaemia/lymphoma' has therefore been used in the literature. 6,20,21 In this study, we intended to evaluate the differences between bone marrow NK/T-cell neoplasms with no extramedullary mass (group 1) and those with extramedullary mass (group 2). Group 1 cases were of the leukaemic form without extramedullary mass, fulfilling the WHO 2017 diagnostic criteria for ANKCL, and commonly had chromosome 7 abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with cytogenetic abnormalities (median 1 month; range 0.4-2 months) had worse survival than those with normal karyotypes (median 3 months; range 0.3-12 months) (P = 0.026; Figure 4B). Group 1 patients with or without cytogenetic abnormalities and group 2 patients with cytogenetic abnormalities had significantly more hazards than group 2 patients with [20],+idic(7)(p14)del (7) (q31q32) [20],-9 [3],-16 [3],der(18)t(18;?)(p11.2;?) [20],-20 [3][cp20] 2 47,X,-X,t(4;6)(q31;p23),+i (7) normal karyotypes in the Cox model with age adjustment (Table S4).…”
Section: L I N I C a L O U T C O M Ementioning
confidence: 99%
“…The aetiology is unknown but the strong association with EBV suggests a pathogenetic role of the virus [ 201 ]. Nevertheless, in the last years, cases of EBV-negative ANKL have been reported [ 210 , 211 ]. EBV-negative ANKL seems to be indistinguishable clinically and pathologically from the EBV-positive cases.…”
Section: Ebv-associated T and Nk-cell Lymphoproliferative Diseasesmentioning
confidence: 99%
“…Little is known about the molecular pathogenesis of ANKL. However, recent studies have identified frequent mutations leading to activation of the JAK/STAT pathway including STAT5B and STAT3 gene mutations [ 211 , 216 ], TP53 mutations have also been reported [ 210 ].…”
Section: Ebv-associated T and Nk-cell Lymphoproliferative Diseasesmentioning
confidence: 99%